DESAIN INOVASI FURNITURE BERBASIS SENSOR SUARA SUARA PADA PENCAHAYAAN - Zaenal Arifin (SULUH: Jurnal Seni Desain Budaya, 2022)
e development of the business world in the furniture sector is very rapid in the competition for product design. Every day, every hour, minute and second, creative ideas always appear in creating fresh and attractive designs, on the one hand the development of designs continues to increase and market demand continues to demand something new, it will have an impact on the accumulation of wood waste in every production, especially wood furniture. there are many in Jepara, this raises a lot of thoughts that need to be studied in a special study in creating something interesting from the wastes of the furniture industry, a good basic idea is needed in formulating a good design by looking at the market and combining materials to provide the best value in the final result. Through this research with an innovative design of furniture based on sensor suaras in lighting, an idea will be created according to market demand and innovative steps to deal with the times and very comprehensive market competition.